Dad camp : a novel - Porter, Evan S. ([New York] : Dutton, 2024)
"A heartwarming novel about a dad who whisks his 11-year-old daughter away to a week-long father-daughter camp to bond before he loses her to teenage girlhood entirely, and ends up reconnecting with the person he gave up to become a Super Dad"--
Keywords: Domestic fiction; Novels